Serum magnesium at 18-20 weeks of gestation: can it be a predictor of gestational hypertension and fetomaternal outcome? - Kathiresan, Sasikala; Sanjevrajah, Agalya Angelina; Kathiresan, Jeyashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive disorders of pregnancy (HDP) is a major cause of maternal, fetal morbidity and mortality complicating 10% of all gestations. As effective treatments are very limited, prediction of HDP occurrence is most importance. Though many biomarkers have shown relationship with HDP, serum magnesium (Mg) has shown better predictor as involved in maintaining vascular contractility, tone. This study is intended to analyse incidence of GHT and fetomaternal outcome in pregnant women with normal and low serum magnesium level measured at mid trimester (18-20 weeks). Methods: A total of 105 consecutive singleton pregnant women in between 18-20 weeks of gestation attending OBG outpatient department were enrolled. After obtaining the informed consent, structured proforma was used to collect demographic, clinical details. Serum magnesium was measured by the colorimetric method and study participants were divided into two groups based on Mg cut off 1.5 mg/dl and followed up throughout pregnancy for fetomaternal outcome. Results: This study results revealed that 35.2% (37/105) pregnant women had serum Mg level < 1.5 mg/dl and mean value of Mg of all participant is 1.7 mg/dl, just above the lower limit. During follow-up of these two groups, statistically significant correlation between serum Mg levels (< 1.5 mg/dl) with GHT (8/12) occurrence and pre term birth was found. Other fetomaternal outcome not had significant correlation. Conclusions: As per the findings, serum Mg concentration measurement in between 18-20 weeks can be considered as a one of the predictors for subsequent occurrence of maternal outcome of GHT and fetal outcome of pre-term birth.